Digitalization and configurational effects on regional income inequality: analysis of panel data from 134 economies - Hu, Shuigen; Jie, Yulong; Zhu, Siling (Technological and Economic Development of Economy, 2025)
The literature on the impact of digitalization on regional income disparities is fragmented and contentious. Drawing on complex systems perspective and configurational theory, this paper analyses the configurational effects of digitalization factors embedded in specific contexts on regional income disparities, using a sample of 134 economies from 2012 to 2021, employing Panel Fuzzy-Set Qualitative Comparative Analysis (Panel fsQCA) and Necessary Condition Analysis (NCA). This paper identifies four context-specific configurational patterns through which digitalization reduces regional income disparities. While no single condition emerges as a strictly necessary condition, digital inclusion and digital finance demonstrate broad positive effects across configurations. Although digital transformation cannot guarantee reduced disparities, severe digital deficiency consistently leads to widening regional income disparities. At the same time, this paper discovers previously unnoticed causal mechanisms and captures the dynamic  trends and spatial characteristics of digitalization’s impact. These findings offer diverse,adaptable insights for regional common prosperity.First published online 23 September 2025